2015
DOI: 10.1080/00131881.2015.1085235
|View full text |Cite
|
Sign up to set email alerts
|

Assessing 10- to 11-year-old children’s performance and misconceptions in number sense using a four-tier diagnostic test

Abstract: Background: Number sense is a key topic in mathematics education, and the identification of children's misconceptions about number is, therefore, important. Information about students' serious misconceptions can be quite significant for teachers, allowing them to change their teaching plans to help children overcome these misconceptions. In science education, interest in children's alternative conceptions has led to the development of three-and four-tier tests that not only assess children's understandings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
1
28
0
9
Order By: Relevance
“…In his study, a slightly higher score was observed for TDT . This finding is similar to the studies by Li and Yang (2010), Yang, Li and Lin (2008), and Yang and Lin (2015). In these studies, it was found that the rate of correct responses was higher in TDCT (I) than in TDCT (II) .…”
Section: Discussionsupporting
confidence: 90%
“…In his study, a slightly higher score was observed for TDT . This finding is similar to the studies by Li and Yang (2010), Yang, Li and Lin (2008), and Yang and Lin (2015). In these studies, it was found that the rate of correct responses was higher in TDCT (I) than in TDCT (II) .…”
Section: Discussionsupporting
confidence: 90%
“…To improve the assessment features of MC items, researchers have explored different designs including two-tier multiple choice (TTMC) [14], ordered multiple choice (OMC) [15], multiple-tier multiple choice (3 or more tiers) [16][17][18][19][20], and test combination analysis [21]. This study will focus on the TTMC design, which was first proposed by Treagust [14] and has gained popularity in recent years [12,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Tes diagnostik dengan pendekatan miskonsepsi dapat dilakukan untuk mengukur level miskonsepsi mahasiswa berdasarkan pengalaman sehari-hari. Tes diagnostik yang biasanya dilakukan antara lain menggunakan Certainty Respons Index (Andriani et al, 2015;Fitria, 2014), 3-Tier Diagnostic Test (Fitrianingrum et al, 2017;Pesman, 2005;Wahyuningsih., 2018) dan 4-Tier Diagnostic Test (Kaltacki-Gurel et al, 2017Yang & Lin, 2015).…”
Section: Pendahuluanunclassified